2005
DOI: 10.1016/j.febslet.2005.06.031
|View full text |Cite
|
Sign up to set email alerts
|

ZD1839 (Gefitinib, ‘Iressa’), an epidermal growth factor receptor‐tyrosine kinase inhibitor, enhances the anti‐cancer effects of TRAIL in human esophageal squamous cell carcinoma

Abstract: The EGF (epidermal growth factor) receptor-tyrosine kinase inhibitor ZD1839 (Gefitinib, ÔIressaÕ) blocks the cell signaling pathways involved in cell proliferation, survival, and angiogenesis in various cancer cells. TNF-related death apoptosis inducing ligand (TRAIL) acts as an anticancer agent. We investigated the antitumor effects of ZD1839 alone or in combination with TRAIL against human esophageal squamous cell cancer (ESCC) lines. Although all ESCC cells expressed EGF receptor at a protein level, the eff… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

6
40
1

Year Published

2006
2006
2023
2023

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 67 publications
(47 citation statements)
references
References 27 publications
6
40
1
Order By: Relevance
“…Investigators have confirmed the relationship between EGFR status and STAT3, and between the EGFR status and cytokine expression, such as IL-6, IL-8 or TNF· (19,20,(29)(30)(31)(32)(33)(40)(41)(42). Our results show the relationship between EGFRm and EGFR-c immunoexpression, and the mRNA amplification level, obtained by PCR for STAT3 as well as the concentrations of proinflammatory/regulatory cytokines secreted by PBMCs, especially IL-8, IFNÁ and TNF·.…”
Section: Discussionsupporting
confidence: 56%
See 1 more Smart Citation
“…Investigators have confirmed the relationship between EGFR status and STAT3, and between the EGFR status and cytokine expression, such as IL-6, IL-8 or TNF· (19,20,(29)(30)(31)(32)(33)(40)(41)(42). Our results show the relationship between EGFRm and EGFR-c immunoexpression, and the mRNA amplification level, obtained by PCR for STAT3 as well as the concentrations of proinflammatory/regulatory cytokines secreted by PBMCs, especially IL-8, IFNÁ and TNF·.…”
Section: Discussionsupporting
confidence: 56%
“…In squamous cell head and neck carcinomas (HNSCC), constitutively active STAT3 has been shown to be associated with EGFR signaling and deregulated cell growth (20,21,27,28). Nevertheless, several studies have been reported, which demonstrate the interaction of proinflammatory cytokines with EGFR as well as the effects of antitumor cytokine connected with the activation of cell death program (29)(30)(31)(32)(33). It is known that TNF· is capable of activating tumor cell apoptosis through receptor clustering and the stimulation of caspases (caspase-8) (31,32).…”
Section: Introductionmentioning
confidence: 99%
“…Gefitinib has been shown to induce growth arrest of human esophageal cancer cell lines [46,47]. Teraishi et al [46] found no correlation between response to gefitinib and the level of EGFR expression, but in gefitinib-responsive cells they observed a dose-dependent increase in cell cycle arrest at the G 1 phase.…”
Section: The Role Of Egfr In Esophageal Cancermentioning
confidence: 99%
“…Teraishi et al [46] found no correlation between response to gefitinib and the level of EGFR expression, but in gefitinib-responsive cells they observed a dose-dependent increase in cell cycle arrest at the G 1 phase. Moreover, the antitumor effect of the death receptor ligand tumor necrosis factor-related apoptosis-inducing ligand (TRAIL) was enhanced by gefitinib treatment, even in cells considered to be TRAIL resistant [46]. The mechanism for this was shown to involve inhibition of EGFR-mediated Akt phosphorylation by gefitinib, leading to Bcl-xL inactivation and caspase-9 activation, thereby promoting apoptosis of cells through a mitochondrial-dependent apoptotic pathway.…”
Section: The Role Of Egfr In Esophageal Cancermentioning
confidence: 99%
“…Gefitinib has broad anti-tumour effects against various types of solid tumours, including non-small cell lung cancer, breast, ovarian cancer and head cancers (10). Although the induction of apoptosis has been considered as a major mechanism in the anti-cancer effects of gefitinib, most of these effects are EGFR-dependent.…”
Section: Introductionmentioning
confidence: 99%